Limited impact of abiotic stress on surfactin production in planta and on disease resistance induced by Bacillus amyloliquefaciens S499 in tomato and bean. Issue 3 (29th July 2013) - Pertot, Ilaria; Puopolo, Gerardo; Hosni, Taha; Pedrotti, Lorenzo; Jourdan, Emmanuel; Ongena, Marc
Abstract: Understanding how temperature and water stress affect protocooperation between plants and beneficial rhizobacteria may enhance the efficacy of biocontrol agents in reducing plant diseases. However, little is known about the impact of these factors on biocontrol mechanisms and effectiveness, especially when provided by beneficial Bacillus spp. This work aimed to evaluate the influence of low/high temperature combined with a normal and reduced water regime on the interaction between Bacillus amyloliquefaciens strain S499 and plants, resulting in the induction of systemic resistance (ISR). A reduction in ISR level was observed when plants were subjected to stress before bacterization; however, root treatment with S499 prior to stress exposure attenuated this negative effect. Colonization of S499 during exposure to temperature/water stress allowed the three crops to conserve their overall ability to mount defense lines to a similar degree at all the temperatures tested. Further investigation revealed that relative production of surfactin by S499 was clearly enhanced at low temperature, making it possible to counter‐balance the negative effect on traits associated with rhizosphere fitness (colonization, motility, and biofilm formation) observed in vitro in cold conditions. This work thus represents a first step in deciphering the effect of high/low temperatures and/or drought on key plant–microorganism interactions culminating in ISR.